Canada : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2001)
The Canadian economy ended the 1990s with a very strong performance, underpinned by the sound macroeconomic policies put in place during the decade. The Bank of Canada raised interest rates markedly in 2000 as estimates of slack in the economy were narrowing rapidly. Executive Directors agreed with the authorities' view that monetary policy should be set to reflect economic conditions in Canada and should aim to allow the economy to seek its productive potential without compromising the official inflation target.